Goodbye Earl : a revenge novel - Cross-Smith, Leesa, 1978- (New York : GCP, Grand Central, 2023)
"Taking inspiration from the infamous, empowering song, Goodbye Earl follows four best friends through two unforgettable summers, fifteen years apart. In 2004, Rosemarie, Ada, Caroline, and Kasey are in their final days of high school and on the precipice of all the things teenagers look forward to when anything in life seems possible ... from falling in love, to finding their dream jobs, to becoming who they were meant to be. In 2019, Kasey has returned to her small Southern hometown of Goldie for the first time since high school--and she still hasn't told even her closest friends the truth of what really happened that summer after graduation, or what made her leave so abruptly without looking back. Now reunited with her friends in Goldie for a wedding, she's determined to focus on the simple joy of being together again. But when she notices troubling signs that one of them might be in danger, she is catapulted back to that fateful summer. This time, Kasey refuses to let the worst moments of her past define her; this time, she knows how to protect those she loves at all costs. Uplifting, sharp-edged, and unapologetic, Goodbye Earl is a funeral for all the "Earls" out there--the abusive men who think they can get away with anything, but are wrong--and a celebration of enduring sisterhood"--
Keywords: Female friendship -- Fiction; Secrecy -- Fiction; Revenge -- Fiction; Summer -- Fiction; Abused women -- Fiction; Abusive men -- Fiction; Thrillers (Fiction); Psychological fiction; Novels